Design and development of an innovative apparatus for producing a spiral catalyst substrate for catalytic converter - Hassan, Mohd Fahrul (2009)
Spiral catalyst substrate is one of the substrate types for catalytic converter and has high geometric surface area. It is to provide support structure in which the washcoat and the catalyst are applied. Currently, an issue of considerable interest in producing the substrate from a thin sheet metal with a thiclmess O.l1mm and using FeCrAI material has become a trend. Existing patented apparatus overseas use a complicated system and specific details are scarce. Therefore, this research presents the works in designing and developing an innovative apparatus based on a systematic approach of Pahl and Beitz's model of design process. Furthermore, Finite Element Method (Dynaform) was applied for the forming analysis of a trapezoid cell of corrugation on a thin sheet metal and spiral shape of corrugated sheet metal. These works provide the conceptual designs for the apparatus of Corrugated Tool for corrugation process and Spiral Tool for spiral process. The selected conceptual design was established by developing a model of the apparatus. A rule of thumb for requiring unloaded diameter of corrugated sheet metal in spiral shape was derived. Forming Limit Diagram (FLD) shows that the thin sheet metal was successfully formed without any cracking and Thiclmess Diagram shows that the thiclmess of the formed thin sheet metal was in safe thickness. The springback effect that occurs during the sheet metal in spiral shape was solved using the developed casing. The designed apparatus of Corrugated Tool and Spiral Tool were fabricated and optimization was performed by producing the spiral catalyst substrate. The innovative apparatus for producing the full scale of spiral catalyst substrate were successfully designed and developed.